A Systematic Literature Review of English Reading Strategies among EFL Undergraduate Students in Indonesian - Aldera L Gazela; Amirul Mukminin; Masbirorotni Masbirorotni (FKIP - Universitas Riau, 2026)
This paper presents a systematic literature review examining the effectiveness of various reading strategies tailored for English as a Foreign Language (EFL) students with limited proficiency in Indonesian higher education contexts. Although reading is a foundational skill in EFL learning, many studies report persistent difficulties in reading comprehension among Indonesian EFL undergraduates. This review aims to identify practical and research-supported strategies that enhance reading comprehension and academic reading performance. Guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, this study analyzed 30 peer-reviewed journal articles and institutional studies published between 2018 and 2023 in the Indonesian EFL context. The synthesis highlights the prominence of cognitive and metacognitive strategies, particularly planning, monitoring, summarizing, and self-questioning. In addition, explicit strategy instruction, including KWL and technology-assisted reading practices, was found to positively influence students’ reading achievement, motivation, and self-efficacy. This review underscores the importance of systematic, strategy-based instruction in supporting EFL undergraduate students’ academic reading development.